ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SEKOLAH MENENGAH PERTAMA DI JEMBER DALAM MENYELESAIKAN SOAL PELUANG PADA PEMBELAJARAN BERBASIS LESSON STUDY LEARNING COMMUNITY BERDASARKAN KECERDASAN EMOSIONAL - Nasrul, Alif Rahman; Hobri, H; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2019)
High order thinking skill is the ability to complete the tasks where there is no algorithm that have been taught, that need justification or explanation and probably have more than one solution probability. High thinking skill ability is the ability that consists of analysis, evaluation and creation. Emotional intelligence is the individual intelligence in recognizing self-emotion, motivate yourself, control others emotion and foster relationships with others. Lesson study learning community is the collaborative learning from Japan. The aim of this research is to describe the process of student’s high order thinking skill in solving probability problem on LSLC based learning on emotional intelligence. The subject of this research started from giving emotional intelligence questionnaire, next the learning activity based on LSLC where the students work collaboratively on high order thinking questions on the students’ worksheet that consists of 3 questions covering question number 1 is question of analyzing, question number 2 is question of evaluating and question number 3 is question of creating, it was obtained the subject of 1 student with low emotional intelligence, 1 student with moderate emotional intelligence and 1 student with high emotional intelligence. From those three subjects, it was obtained 1 student with high emotional intelligence that has high order thinking skill, while 1 student with moderate emotional intelligence and 1 student with low emotional intellegence that did not have high order thinking skill. Keywords: HOTS, high order thingking skill, LSLC, lesson study learning community, emmotional intellegen, probability